Enlisting friends to reduce sexual victimization risk: There's an app for that… but nobody uses it. Issue 8 (17th November 2018) - Blayney, Jessica A.; Jenzer, Tiffany; Read, Jennifer P.; Livingston, Jennifer A.; Testa, Maria
ABSTRACT: Objective : The Circle of Six (Co6) phone application (app), winner of the White House's Apps Against Abuse Challenge, seeks to incorporate friends into sexual victimization risk reduction. Despite its growing presence on college campuses, the feasibility/acceptability of the app to college women is unknown. This mixed methods study sought to fill this gap.Participants : College women ( n = 44) participated in summer/fall 2015.Methods : Participants completed questionnaires, used the Co6 app for 2 months, and returned to report their experiences.Results : Consistent with the app's aim, women reported greater intentions to help friends versus strangers in sexually aggressive situations. However, app use was low over follow-up. Reasons women gave for not using the app included redundancy with existing smart phone features and discomfort with group messaging. Some saw the app as an emergency only resource.Conclusions : The Co6 app may not meet the real world needs of college women.